The effects of screen time among Icelandic adolescents in relation to physical activity and well-being - Steingerður Hauksdóttir 1996- (2019)
Technology is growing every day and adolescents are spending more time now on their screen devices than ever. Previous studies indicate that too much screen time can have bad effects on well-being and decrease exercising. The aim of the current study was to examine screen time among Icelandic adolescents along with gender in relation to their well-being and physical activity. Three hypotheses were suggested. First, that too much screen time causes adolescents to spend less time exercising. Second, that adolescents that spend more time using screen devices have worse well-being compared to adolescents that use screen devices less. Third, that there was a gender difference, that similar screen time had different effects on boys and girls when it came to their well-being and exercising. Participants were 2106 students, 13-16 years old from elementary schools in Iceland, 1071 boys and 1017 girls. The results showed that both girls and boys that spent more time on screen devices exercised less. Results also showed that adolescents that spent less time on screen devices scored higher on the well-being scale compared to adolescents that had more screen time. Screen time had more effect on the girl’s well-being, however, both genders were affected by screen time. Keywords: screen device, screen time, physical activity, well-being, gender differences Tæknin fer vaxandi með hverjum degi sem líður og unglingar eyða meiri tíma í skjátækjum nú en áður. Fyrri rannsóknir gefa til kynna að of mikill skjátími geti haft neikvæðar afleiðingar á vellíðan og dregið úr hreyfingu. Markmiðið með núverandi rannsókn var að rannsaka skjátímanotkun á meðal íslenskra unglinga í sambandi við vellíðan þeirra og líkamlega hreyfingu. Þrjár tilgátur voru settar fram. Sú fyrsta var að of mikill skjátími veldur því að unglingar hreyfi sig minna. Önnur tilgáta var að unglingar sem eyða meiri tíma í skjátæki líði verr en unglingum sem nota skjátæki minna. Þriðja tilgáta var að það væri kynjamunur, að svipaður skjátími hafi mismunandi áhrif á ...